Analisis Respons Mahasiswa Program Studi Biologi dan PPG Melalui Perkuliahan Online Selama Masa Covid-19 - Paulus Taek (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2021)
The Covid-19 pandemic hitting the world in early 2020 killed 534.484 people and also caused 11,423,843 confirmed cases of people even if 6. 6.473.335 people have experienced recovery (Tuti et al., 2021). To prevent the spread of Covid-19, The Indonesian Government implements social distancing and requires all activities and public services online from home, including learning. UNDANA as one of the university in Indonesia applies such a strategy based on Surat Edaran Rektor Undana No.: 1699/UN. 15.1/TU/2020. Such lectures certainly bring advantages and disadvantages for students. The impact can be known from the responses of the extracted research subjects. The subjects of this research were students of the Biology Study Program who programmed Animal Physiology, Biochemestry and PPG students who programmed Developmental and Animal Physiology, particularly those concerning enzymes, hormones, and metabolism with a total of 48, 37, and 27, respectively. The problem in this research is how they respond to the implementation of this lecture strategy? The purpose of this research is to find out their response about the lecture strategy that is being carried out. The data of this research are all their opinions in response to the reason for not understanding all the material presented, unable to give proper answer, cannot think critically to express their thoughts effectively and coherently. The results of the analysis of all responses as data show that: (1) 69 individuals (61. 607%) appreciate government policies unconditionally; (2) 31 individuals (27.679%) disagree; (3) 12 individuals (10.714%) forced to do so because they have no other choice, (4) 79 individuals (70. 53%) said it was not effective at all, (5) 33 individuals (29.46%) said it was effective, 12 individuals (10%) said it was conditionally effective provided that students tried to explore the materials that had been taught by asking for additional explanations from the lecture outside of class hours to overcome the obstacles faced, (6) 87 individuals (77.679%), approved the implementation of such a lecture strategy (E-Learning, LMS, WA Group, Google Meet, Zoom Meeting) because of the benefits obtained by students, (7) 22.321% (25 individuals) disagreed because it was not profitable. All respondents also said: (1) effective communication was not implemented during lectures due to network disruptions as a result of weather or location of residential areas that were not covered by the network, (2) the government’s decision to conduct this lecture strategy is the best way (very good) to prevent losing the moment of obtaining lecture material during the Covid-19 pandemic.